Personal Financial Management Among Oil Palm Independent Smallholders in Batu Pahat - Samsuddin, Hidayah; Omar, Abdul Jalil; Omar, Siti Sarah (Research in Management of Technology and Business, 2020)
Oil palm is the largest commodity in Malaysia while independent smallholder farmers are major contributor to the country’s oil palm industry with the biggest involvement of rural population in agriculture activities. However, these independent smallholder farmers are facing serious financial management issues due to volatility of oil palm prices in the global market. This paper explores the elements of good financial management to measure the level of financial management among independent smallholders. Methodology used is through document analysis and exploration from past studies by researchers that relate to the financial management among independent smallholders. The elements of good financial management provide a reference for developing a framework to help independent smallholders improve their financial well-being.